Pengembangan Aplikasi Mobile Learning Berbasis Augmented Reality Materi Bangun Ruang - Anam, Khaerul; Wiradharma, Gunawan; Prasetyo, Mario Aditya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this research is to develop and conduct a feasibility test of mobile learning applications based on augmented reality materials. The benefit of this research is knowing the steps taken in developing the application. The research method used is research and development (R&D) with a quantitative descriptive research approach with a questionnaire as a data collection technique. The stages of research and development are in accordance with the theory put forward by Borg & Gall. This study focuses on the application development section which consists of two stages. The first stage is the initial trial to create content and application views. The second stage is the feasibility of the application according to linguists, materials and media experts. The results of the study show that the overall average feasibility of this mobile learning media is 85.4% with the interpretation of